2019
DOI: 10.1093/ejcts/ezz184
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgical approaches to left main and left anterior descending coronary artery revascularization are superior compared to first- and second-generation drug-eluting stents: a network meta-analysis

Abstract: OBJECTIVES There are a number of minimally invasive approaches to revascularization of coronary artery disease that involve the left main or proximal left anterior descending artery; however, studies to date provide mixed results. METHODS A Bayesian network meta-analysis was performed to compare early and late postoperative outcomes between percutaneous coronary intervention with first- and second-generation drug-eluting sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…However, the revascularization rate at follow-up is more frequent after PCI than after CABG, even in patients with low or intermediate anatomical complexity [3]. In a recent meta-analysis, Indja B. et al [26] confirmed that MIDCAB for LAD remains superior to first-or second-generation PCI with drug eluting stent in term of long-term freedom from myocardial infarction and target vessel revascularization as well as of improved overall long-term survival.…”
Section: Commentmentioning
confidence: 99%
“…However, the revascularization rate at follow-up is more frequent after PCI than after CABG, even in patients with low or intermediate anatomical complexity [3]. In a recent meta-analysis, Indja B. et al [26] confirmed that MIDCAB for LAD remains superior to first-or second-generation PCI with drug eluting stent in term of long-term freedom from myocardial infarction and target vessel revascularization as well as of improved overall long-term survival.…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, integrated PCIs provide the patient with the least invasive HCR option, achieving complete revascularization of all diseased coronary arteries. The use of the second-generation DES is of paramount importance in the treatment of non-LAD coronary pathology and provides a valuable alternative to surgical revascularization of non-LAD targets using a venous graft, the latter being notorious for future atherosclerotic degeneration resulting in high short-and long-term failure rates [5][6][7].…”
Section: Hybrid Revascularizationmentioning
confidence: 99%
“…A metaanalysis comparing MIDCAB to classic off-pump techniques and drug-eluting stents found no difference between the two surgical techniques and again demonstrated best outcomes with CABG. 31 The main findings of 2020 publications on surgical treatment for CAD are as follows:…”
Section: Minimally Invasive Cabgmentioning
confidence: 99%